2017
DOI: 10.1142/s0219498817500852
|View full text |Cite
|
Sign up to set email alerts
|

Quotients of degenerate Sklyanin algebras

Abstract: Abstract. In this paper it is shown how the Heisenberg group of order 27 can be used to construct quotients of degenerate Sklyanin algebras. These quotients have properties similar to the classical Sklyanin case in the sense that they have the same Hilbert series, the same character series and a central element of degree 3. Regarding the central element of a 3-dimensional Sklyanin algebra, a better way to view this using Heisenberg-invariants is shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In order to find all presentations of four dimensional Sklyanin algebras with the degree 1 part decomposed in four 1-dimensional representations of V 4 , one still needs to allow for base change with the subgroup Aut V4 ( 4 V 1 ). By Schur's lemma, Aut V4 ( 4 V 1 ) ∼ = (C * ) 4 , but the subgroup of scalar matrices C * acts trivially as a Sklyanin algebra is graded. Let…”
Section: Quadratic Sklyanin Algebras Of Global Dimension Fourmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to find all presentations of four dimensional Sklyanin algebras with the degree 1 part decomposed in four 1-dimensional representations of V 4 , one still needs to allow for base change with the subgroup Aut V4 ( 4 V 1 ). By Schur's lemma, Aut V4 ( 4 V 1 ) ∼ = (C * ) 4 , but the subgroup of scalar matrices C * acts trivially as a Sklyanin algebra is graded. Let…”
Section: Quadratic Sklyanin Algebras Of Global Dimension Fourmentioning
confidence: 99%
“…In addition, it will be shown that Cc 3 is the trivial representation of H 3 , Cc 4 is the trivial representation of H 2 and CΩ 1 + CΩ 2 is isomorphic to the unique simple 2-dimensional representation of H 4 coming from the quotient map H 4 / / / / H 2 that will be explained below. In fact, for c 3 the connection between c 3 and the Sklyanin algebra Q 3 (E, 2τ ) will be explained, finishing the discussion started in [4] and [5].…”
Section: Introductionmentioning
confidence: 97%